Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1111/j.1076-7460.2003.02010.x
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulation in the Elderly

Abstract: This review will address the general approach to the management of the typical elderly patient requiring anticoagulation. Most of the data has been derived from studies of patients with nonvalvular atrial fibrillation. Data from postmyocardial infarction trials have also been included. A practical clinical approach to anticoagulation in the elderly is described. Emphasis has been placed on maximizing the benefit and reducing the risk of anticoagulation in the rapidly expanding group of elderly patients aged >/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 51 publications
(47 reference statements)
0
13
0
Order By: Relevance
“…The trial was stopped after 1.1 years when significantly higher rates of ischemic stroke and systemic embolization (7.9% vs. 1.9%) occurred in the combined group (Dhond et al, 2003).…”
Section: Meta-analysismentioning
confidence: 99%
See 4 more Smart Citations
“…The trial was stopped after 1.1 years when significantly higher rates of ischemic stroke and systemic embolization (7.9% vs. 1.9%) occurred in the combined group (Dhond et al, 2003).…”
Section: Meta-analysismentioning
confidence: 99%
“…SP AF III concluded that combination therapy showed no therapeutic benefit and dose-adjusted warfarin therapy was more effective for the patient without causing increased haemorrhagic complications (Dhond et al, 2003;Halperin, 2005;Hart et al, 2007).…”
Section: Meta-analysismentioning
confidence: 99%
See 3 more Smart Citations